2004
DOI: 10.3171/ped.2004.100.5.0506
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic disconnection for hypothalamic hamartoma with intractable seizure

Abstract: Although intractable epilepsy associated with hypothalamic hamartoma (HH) can be controlled by microsurgical resection of the lesion, excision of deep-seated lesions is often associated with morbidity and mortality. Endoscopic disconnection is less invasive and seems to be well suited for this indication. The authors discuss the role of endoscopic-assisted surgery in the management of HH-induced seizures. Four patients with HH-related intractable gelastic seizure underwent endoscopic disconnection surgery. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
0
47
0
2
Order By: Relevance
“…79,82 Over the last 15 years, depth electrode studies from a small number of additional patients with HH have confirmed that ictal events manifested by gelastic seizures clearly arise from the HH itself. 31,58,67 Interestingly, habitual seizures can be reproduced by electrical stimulation of the depth electrode contacts within the HH in some of these patients. 31,58,67,79 Strong evidence for the intrinsic epileptogenesis of the HH was further strengthened by metabolic neuroimaging studies.…”
Section: Depth Electrode Recordingmentioning
confidence: 99%
“…79,82 Over the last 15 years, depth electrode studies from a small number of additional patients with HH have confirmed that ictal events manifested by gelastic seizures clearly arise from the HH itself. 31,58,67 Interestingly, habitual seizures can be reproduced by electrical stimulation of the depth electrode contacts within the HH in some of these patients. 31,58,67,79 Strong evidence for the intrinsic epileptogenesis of the HH was further strengthened by metabolic neuroimaging studies.…”
Section: Depth Electrode Recordingmentioning
confidence: 99%
“…9,35,37 Endoscopic disconnection can be performed as well. 8 Radiofrequency ablation has also been described. 17,18,25,36 Surgical morbidity is limited overall, especially considering the challenging neural and vascular anatomy surrounding the HH, but includes thalamocapsular infarcts with resulting hemiparesis or hemiplegia, oculomotor palsy, visual field deficits, short-term memory deterioration, hyperphagia, hypothyroidism, and diabetes insipidus.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…9,13,24,35,37,44,45 Substantial seizure improvement following resection, disconnection, or ablation is further proof of the intrinsic epileptogenesis of HHs and the need for a direct approach to produce seizure relief. [2][3][4]8,9,[12][13][14][16][17][18]24,25,28,35,36,[44][45][46][47][48]51,52 The degree of seizure control is linked to the extent of the surgical intervention. Incomplete resection, disconnection, or ablation of the HH can be associated with incomplete seizure control, whereas freedom from seizures may be induced by a more aggressive approach.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…They found the terminal balloon which resembles the terminal myelocystocele of human [8]. In 2004, Dr. Joong-Uhn Choi and his team published an article regarding their experience on the endoscopic disconnection for hypothalamic hamartoma with intractable seizure [9]. Dr. Joong-Uhn Choi invented an endoscopic approach, and Dr. Rekate adopted this method for his own cases and later reported a large series [10].…”
Section: Two Models Of Volunteer Medical Service In Sudanmentioning
confidence: 99%